Comparison of Student Learning Outcomes Assessment Practices Used Globally - Shani D. Carter (Athens Institute for Education and Research, 2015)
Student learning outcomes assessment examines whether programs cover the material stated in their learning goals, whether students are learning the material, and the impact on student retention, graduation, post-graduation outcomes, and institutional accreditation, with the aim of providing faculty with data that can be used to help programs evolve or improve. While there is a plethora of research regarding effective methods of assessment used in the United States, little has been written regarding cross-national comparisons of assessment methodologies. This paper examines the current state of assessment in several nations and regions, and draws parallels in practices across countries. A literature search using the term "outcomes assessment" yielded 228 articles, of which, only 35 described practices outside the United States. Generally, searches on the terms "outcomes assessment" and "global" tend to return studies of outcomes assessment of teaching about global issues as it is practiced in the United States, rather than results about outcomes assessment practices used in other countries.